TEKNOSOCIALE SAMMENFILTRINGER: Redaktionelt forord - Barrett, Barbara Ann; Bruun, Birgitte; Brogård Kristensen, Dorthe; Madsen, My; Møhl, Perle; Sørensen, Bo (Tidsskriftet Antropologi, 2021)
Redaktionelt forord.